2008
DOI: 10.1007/s10549-008-9984-6
|View full text |Cite
|
Sign up to set email alerts
|

Weight changes after adjuvant treatment in Korean women with early breast cancer

Abstract: This study shows that Korean women with early breast cancer do not gain weight after adjuvant treatment. Further studies are needed to determine differences between Asian and Western women in terms of weight changes and prognosis in early breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 32 publications
(47 reference statements)
7
58
2
Order By: Relevance
“…Chemotherapy has been associated with weight gain among breast cancer survivors in some [1416, 21, 39, 40] but not in all studies [22, 28, 32, 41]. A significant association was not observed between chemotherapy and weight gain following a breast cancer diagnosis after adjustment for other factors.…”
Section: Discussionmentioning
confidence: 96%
“…Chemotherapy has been associated with weight gain among breast cancer survivors in some [1416, 21, 39, 40] but not in all studies [22, 28, 32, 41]. A significant association was not observed between chemotherapy and weight gain following a breast cancer diagnosis after adjustment for other factors.…”
Section: Discussionmentioning
confidence: 96%
“…Weight gain reported as a symptom or bothersome symptom in Year One ranged from 18 to 52 % [40,51] and in Year Five from 7 to 55 percent [35,37]. Most studies did not provide specific amounts of weight change; however, in the few studies that did provide specific amounts, mean weight change reported in Year One ranged from -0.01 to 1.8 kg [56,66]. Some studies reported the proportion of women who lost weight during the first two years and the proportion whose weight was stable, in addition to the proportion who gained weight [32,38].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported significantly greater effect sizes for weight gain in the ET group as compared to no ET at 6, 12, and 18 months from breast cancer diagnosis (p \ 0.01) [55], while another study reported significantly less weight loss at Year One in the ET as compared to the no-ET group (p = 0.007) [56].…”
Section: Unspecified Etmentioning
confidence: 99%
“…It is important to know that all studies showing evidence of significant weight gain following adjuvant treatment were reported from the United States and Western European countries. Such evidence has not been observed in Korean women with early BC suggesting that some other ethnic, biologic or genetic factors which might play a role [24].…”
Section: Introductionmentioning
confidence: 89%